Speech Act of the Main Character in “The Hobbit: An Unexpected Journey” - Balango, Mery (Research Review: Jurnal Ilmiah Multidisiplin, 2022)
Speech act is the utterance that speakers performs or speaker says in every speech. One of the benefits that can be learned on this study is help us to understand what hidden massage in every utterance. This research is aimed to explore the speech act in a fantasy film which is titled The Hobbit: An Unexpected Journey, The researcher pick this film as the object of research because this is a good film and the researcher finds some illocutionary acts. Moreover, the act of doing something as commonly known as Illocution, is a speech act that aimed at doing something (Parera, 1991:151). The concept of illocutionary act is expected to cover up the "act of saying something" in the "full normal sense". According to Austin the "full normal sense" can be explained as "the utterance of certain words in a certain construction, and the utterance of them with a certain 'meaning' in the favourite sense of that word". According to Searle (Mey. 1994:163) there are five types of illocutionary act, there are: representatives, directives, commisives, expressive, and declaratives. While this research will be focused on Directives. Speech act is one of important thing to learn, because by learning this we can improve our sense or can be easily understand what are the massage that hidden in every single speech or utterance in conversation or movie. As the focus of the research which is the directives speech act of The hobbit: An unexpected journey. The researcher is going to analyze what are the speech act that exist in that movie. This research is going to be a library research with qualitative method, this is going to be focused on illocutionary acts based on Searle that will be found on The hobbit: An unexpected journey movie script.